Implementasi Prinsip Kerja Generator pada Alat Peraga Program Eduwisata di Pos Konservasi Energi Taman Rekreasi Sengkaling Universitas Muhammadiyah Malang: Implementation of the Generator Working Principle in the Props of the Eduwisata Program of Taman Rekreasi Sengkaling Universitas Muhammadiyah Malang in Energy Conservation Station - Rahmandhika, Andinusa; Mokhtar, Ali; Astuti, Ary Dwi; Zakaria, Arie (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Taman Rekreasi Sengkaling (TRS) is a business unit owned and managed by Universitas Muhammadiyah Malang (UMM). It provides entertainment and educational (eduwisata) facilities for visitors. Students' use of the props in the Energy Conservation Station TRS UMM prompted the need for repair and maintenance. Therefore, some of the materials that need props cannot be practiced. Moreover, knowledge on energy has been developed that TRS UMM requires another prop for the eduwisata program in Energy Post. Therefore, the problem faced by TRS UMM, especially in Energy Post, is the need for additional props to serve as facilities for the eduwisata program for visitors. The solution offered to this problem is to provide this facility with props for the Energy Conservation Station TRS UMM. The props were designed to develop energy knowledge, especially for students' learning, as they aim to help students apply and practice the concepts they learned at school. The design of the props began with building the design and defining the working principle. It was tested before it was applied at Energy Post TRS UMM.